The Use of Self-Expanding Plastic Stents in the Management of Oesophageal Leaks and Spontaneous Oesophageal Perforations. (7th July 2011) - Moyes, L. H.; MacKay, C. K.; Forshaw, M. J.
Abstract : Leakage after oesophageal anastomosis or perforation remains a challenge for the surgeon. Traditional management has been operative repair or intensive conservative management. Both treatments are associated with prolonged hospitalisation and high morbidity and mortality rates. Self-expanding metallic stents have played an important role in the palliation of malignant oesophageal strictures and the treatment of tracheoesophageal fistulae. However, self-expanding metal stents in benign oesophageal disease are associated with complications such as bleeding, food bolus impaction, stent migration, and difficulty in retrieval. The Polyflex stent is the only commercially available self-expanding plastic stent which has been used in the management of malignant oesophageal strictures with good results. This review will consider the literature concerning the use of self-expanding plastic stents in the treatment of oesophageal anastomotic leakage and spontaneous perforations of the oesophagus.